6+7b=6-9b

Simple and best practice solution for 6+7b=6-9b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+7b=6-9b equation:



6+7b=6-9b
We move all terms to the left:
6+7b-(6-9b)=0
We add all the numbers together, and all the variables
7b-(-9b+6)+6=0
We get rid of parentheses
7b+9b-6+6=0
We add all the numbers together, and all the variables
16b=0
b=0/16
b=0

See similar equations:

| -9e=81 | | 6(q+7)=54 | | 4x(3x−6)=11x−35 | | 8.3n+2.06-8n=-2.86-0.3n | | x-2)=-1/4(x-8) | | 14+t/6=22 | | 5=8+-3c | | x/6.2=−2.1 | | 9=2h−5 | | 1/2(16x+4)=20 | | -9-9t=9.9 | | 5x+5=62 | | (x-2)=-1/3(x-8) | | -2(x-1/2)=5x+88 | | 23=3+5g | | -2-x+8=13 | | 10x=(3x+50) | | 2x+7=3x-2x+5 | | 12m=216 | | 15.5r=-77.5 | | 13=|m+2|-3 | | 76=m/9+70 | | 5=b+25/8 | | 18x+4=3x+6 | | 9+3d=2d+4 | | 0.75s-2.25=0.125s+0.25 | | 3.5a=-14 | | 18(1.3)^2x-1=90 | | 4.32x=12.96 | | 3x+6=-4+5x | | -3.5=b/0.2 | | 7x+3=79 |

Equations solver categories